PELAKSANAAN KEPUTUSAN MENTERI PERHUBUNGAN NOMOR 35 TAHUN 2007 TENTANG PEDOMAN DASAR PERHITUNGAN TARIF PELAYANAN JASA BONGKAR MUAT KAPAL DI PELABUHAN SAMARINDA - Syahrina, Syahrina (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTThe implementation of development in Indonesia which aims at the field of economic development, so that trade activities become one of the economic development sectors, its role is always developed. To facilitate the flow of goods and services to support these trading activities, there is a need for adequate transportation facilities, one of which is by sea. The purpose of this process is to find out the Tariff Delivery System for Manpower Services in Loading and Unloading (TKBM) in the Port of Samarinda and to find out the system of loading and unloading personnel in the Port of SamarindaThis type of research is normative legal research by looking at the law and conceptual. By using basic, secondary and non-legal materials. Then legal materials are processed in a deductive and attractive way to be more specific and systematically arranged.The results of this report are the loading and unloading fare system at the port which is regulated by the Minister of Transportation Decree No. 35 of 2007, namely the amount of loading and unloading services from and to ship. Basic services that are used together to provide services speed, speed, cost, speed, cost, speed, cost, speed, cost. The wage system for loading and unloading workloads in Samarinda must be adjusted to the appropriate needs of the components and stages determined by the Minister, can be realized from Law No. 13 of 2003 concerning Manpower Article 88 paragraph (1) that: "every worker / laborer has the right to increase which meets the proper needs of humans. "Keywords: Labor, Unloading, Tariffs, Service Services